Observer Effects on Quantum Randomness: Testing Micro-psychokinetic Effects of Smokers on Addiction-related Stimuli - Maier, Markus Andreas; Dechamps, Moritz Christopher (Journal of Scientific Exploration, 2018)
A vivid discussion revolves around the role of the human mind in the quantum measurement process. While some authors argue that conscious observation is a necessary element to achieve the transition from quantum to classical states during measurement (Wigner, 1963), some go even further and propose a more active influence of the human mind on the probabilities of quantum measurement outcomes (e.g. Atmanspacher, Römer, & Walach, 2002; Penrose & Hameroff, 2011). This proposition was tested in micro-psychokinesis (micro-Pk) research were intentional observer effects on quantum random number generators (RNGs) were investigated. In the studies presented here we extended this line of research and tested the impact unconscious goals on micro-Pk. Our focus was cigarette addiction as an unconscious drive and hypothesized that regular cigarette smokers would influence the outcome of a quantum RNG that determined whether the participant was going to see a smoking-related or a neutral picture. Study 1 revealed strong evidence for micro-Pk (BF = 66.06) supporting the H1. As expected, no deviation from chance was found with non-smokers. In Study 2, a pre-registered highly powered replication attempt, failed to reproduce this result and showed strong evidence for H0 (BF = 11.07). When the data from both studies are combined a remarkable change in effect across time (resembling a combination of appearance followed by decline) can be seen only in the smoker’s subsample. Appearance-and-decline effects were absent in the non-smokers sample and in a simulation. Based on von Lucadou’s Model of Pragmatic Information we suggest that (micro-)Pk effects follow a systematic pattern comparable to a dampened harmonic oscillation. This concept may shed new light on past and future Pk research.